2017
DOI: 10.1039/c7ta01784g
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun WNb12O33 nanowires: superior lithium storage capability and their working mechanism

Abstract: Electrospun WNb12O33 nanowires show high-power capability and long-term cycling performance as an anode material for rechargeable lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 63 publications
4
72
0
Order By: Relevance
“…4,5,13,16,[19][20][21][22] The three-stage anisotropic host-lattice response has been observed in Nb 16 W 5 O 55 by Griffith et al 4 using operando synchrotron XRD, and correlates with the regions of the electrochemical profile. Lattice parameters of Li x Nb 12 WO 33 phases have been reported by Cava et al 13 and Yan et al 20 Both authors observed an anisotropic lattice change after full lithiation (Li 10.7 Nb 12 WO 33 and Li 13 Nb 12 WO 33 , respectively), with an a-c plane contraction and expansion along b. However, the lattice changes between the two studies are not consistent, with Cava Regarding the local structure evolution, only results on Nb 16 W 5 O 55 are available, which clearly show that the MO 6 octahedra become progressively more symmetric as lithium is inserted.…”
Section: Discussion Common Mechanistic Principlesmentioning
confidence: 91%
“…4,5,13,16,[19][20][21][22] The three-stage anisotropic host-lattice response has been observed in Nb 16 W 5 O 55 by Griffith et al 4 using operando synchrotron XRD, and correlates with the regions of the electrochemical profile. Lattice parameters of Li x Nb 12 WO 33 phases have been reported by Cava et al 13 and Yan et al 20 Both authors observed an anisotropic lattice change after full lithiation (Li 10.7 Nb 12 WO 33 and Li 13 Nb 12 WO 33 , respectively), with an a-c plane contraction and expansion along b. However, the lattice changes between the two studies are not consistent, with Cava Regarding the local structure evolution, only results on Nb 16 W 5 O 55 are available, which clearly show that the MO 6 octahedra become progressively more symmetric as lithium is inserted.…”
Section: Discussion Common Mechanistic Principlesmentioning
confidence: 91%
“…The C/2 discharge curves of the three versions of Nb18W8O69 were nominally identical ( Figure 3a), but the irreversible capacity and cycling performance differed ( Figure 3). Nb18W8O69 exhibits similar rate performance to its neighboring cs structure Nb16W5O55 up to 20C with similar Nb14W3O44, 19 and Nb12WO33, 14,15 . Cells were cycled between 3.0 V and a lower voltage cutoff (Vmin) of either 1.2 or 1.0 V, with capacity retention being worse for the wider potential window as expected ( Figure 3c).…”
Section: A B B Amentioning
confidence: 87%
“…However, the cycling current density was limited to only 0.8 A g −1 . AlNb 11 O 29 , [ 42a ] TiNb 24 O 62 , [ 50 ] Nb 12 WO 33 , [ 48 ] Ti 2 Nb 10 O 29 , [ 58 ] and TiNb 2 O 7 nanowires [ 59 ] have also been synthesized by the electrospinning method, and their improved electrochemical performance compared with that of bulk materials has clearly demonstrated the influence of the nanowire architecture on the Li + diffusion rate.…”
Section: Strategies To Enhance the Electrochemical Performancementioning
confidence: 99%